La estrategia de inducción: satisfacción y aprendizaje de los estudiantes en programas virtuales (Memorias Sifored - Encuentros Educación UAN, 2021)
The offer of graduate programs under virtual methodologies is promising in Colombia, and that is why it is necessary to investigate the satisfaction that students have with these kinds of offers, especially when they begin their learning process, how to know, in other word: scenarios of induction. The objective of the study was to determine the satisfaction of the students on the induction strategy (how to know) in relation to their adaptation and learning in two virtual universities, in Colombia. The Lavín (2007) questionnaire was used; within the findings, it was found that 50.8% of the students are satisfied and 43.5% are very satisfied with the institutional induction strategy used, and positive correlations greater than 0.65 were found between the satisfaction variable and the components addressed in said strategy. If the student is satisfied with our educational services, their adaptation, permanence and academic success are made possible.
Keywords: Student’s learning; satisfaction; induction strategy; virtual programs